The Monetary Dynamics of International Adjustment under Fixed and Flexible Exchange Rates - Mundell, Robert A. (Quarterly Journal of Economics, 1960)
I. Introduction, 227. — II. The static system, 229. — III. The dynamic systems, 233. — IV. The crucial role of capital movements, 237. — V. Foreign exchange reserves, 242. — VI. Speculation, 246. — VII. Concluding remarks, 249. — Appendix, 251.